Hepatoprotective action of various partitions of methanol extract of Bauhinia purpurea leaves against paracetamol-induced liver toxicity: involvement of the antioxidant mechanisms. Issue 1 (December 2016) - Zakaria, Zainul; Yahya, Farhana; Mamat, Siti; Mahmood, Nur; Mohtarrudin, Nurhafizah; Taher, Muhammad; Hamid, Siti; Teh, Lay; Salleh, Mohd.
Abstract Background Methanol extract ofBauhinia purpurea L. (family Fabaceae) (MEBP) possesses high antioxidant and anti-inflammatory activities and recently reported to exert hepatoprotection against paracetamol (PCM)-induced liver injury in rats. In an attempt to identify the hepatoprotective bioactive compounds in MEBP, the extract was prepared in different partitions and subjected to the PCM-induced liver injury model in rats. Methods Dried MEBP was partitioned successively to obtain petroleum ether (PEBP), ethylacetate (EABP) and aqueous (AQBP) partitions, respectively. All partitions were subjected to in vitro antioxidant (i.e. total phenolic content (TPC), 2, 2-diphenyl-1-picrylhydrazyl (DPPH)- and superoxide-radicals scavenging assay, and oxygen radical absorbance capacity (ORAC) assay) and anti-inflammatory (i.e. lipooxygenase (LOX) and xanthine oxidase (XO) assay) analysis. The partitions, prepared in the dose range of 50, 250 and 500 mg/kg, together with a vehicle (10 % DMSO) and standard drug (200 mg/kg silymarin) were administered orally for 7 consecutive days prior to subjection to the 3 mg/kg PCM-induced liver injury model in rats. Following the hepatic injury induction, blood samples and liver were collected for the respective biochemical parameter and histopathological studies. Body weight changes and liver weight were also recorded. The partitions were also subjected to the phytochemical screening and HPLC analysis. Results Of all partitions, EABP possessed high TPC value and demonstrated remarkable antioxidant activity when assessed using the DPPH- and superoxide-radical scavenging assay, as well as ORAC assay, which was followed by AQBP and PEBP. All partitions also showed low anti-inflammatory activity via the LOX and XO pathways. In the hepatoprotective study, the effectiveness of the partitions is in the order of EABP>AQBP>PEBP, which is supported by the microscopic analysis and histopathological scoring. In the biochemical analysis, EABP also exerted the most effective effect by reducing the serum level of alanine transaminase (ALT) and aspartate transaminase (AST) at all doses tested in comparison to the other partitions. Phytochemical screening and HPLC analysis suggested the presence of: flavonoids, condensed tannins and triterpenes in EABP; flavonoids, condensed tannins and saponins in PEBP and; only saponins in AQBP. Conclusion EABP demonstrates the most effective hepatoprotection against PCM-induced liver injury in rats. This observation could be attributed to its remarkable antioxidant activity and the presence of flavonoids that might probably act synergistically with other biocompounds to cause the hepatoprotection.